Unlocking prognostic potential: A genomic signature of caloric restriction in patients with epithelial ovarian cancer. - Ori Tal; Tamar Zahavi; Liat Anabel Sinberger; Mali Salmon-Divon (PLoS ONE)
Objectives Epithelial ovarian cancer is a significant contributor to cancer-related mortality in women, frequently recurring post-treatment, often accompanied by chemotherapy resistance. Dietary interventions have demonstrated influence on cancer progression; for instance, caloric restriction has exhibited tumor growth reduction and enhanced survival in animal cancer models. In this study, we calculated a transcriptomic signature based on caloric-restriction for ovarian cancer patients and explored its correlation with ovarian cancer progression. Methods We conducted a literature search to identify proteins modulated by fasting, intermittent fasting or prolonged caloric restriction in human females. Based on the gene expression of these proteins, we calculated a Non-Fasting Genomic Signature score for each ovarian cancer sample sourced from the Cancer Genome Atlas (TCGA) database. Subsequently, we examined the association between this genomic profile and various clinical characteristics. Results The non-fasting genomic signature, comprising eight genes, demonstrated higher prevalence in primary ovarian tumors compared to normal tissue. Patients with elevated signature expression exhibited reduced overall survival and increased lymphatic invasion. The mesenchymal subtype, associated with chemotherapy resistance, displayed the highest signature expression. Multivariate analysis suggested the non-fasting genomic signature as a potential independent prognostic factor. Conclusions Ovarian cancer tumors expressing a "non-fasting" transcriptional profile correlate with poorer outcomes, emphasizing the potential impact of caloric restriction in improving patient survival and treatment response. Further investigations, including clinical trials, are warranted to validate these findings and explore the broader applicability of non-fasting genomic signatures in other cancer types.